D. Lincoln Canfield, Spanish pronunciation in the Americas. The University of Chicago Press, Chicago, 1981; 118 pp. - Quijas Corzo, Patricia (El Colegio de México, 1982)
Se reseñó el libro: Spanish pronunciation in the Americas.